2022
DOI: 10.1177/03000605221126874
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen like protein-1 knockdown suppresses the proliferation and metastasis of TU-686 cells and sensitizes laryngeal cancer to LAG-3 blockade

Abstract: Objective To detect the expression of fibrinogen like protein-1 (FGL-1) in laryngeal cancer and evaluate its effect on tumor proliferation, metastasis, and antitumor immunity. Methods ELISA and immunohistochemistry were performed to detect FGL-1 expression in laryngeal cancer. The effects of FGL-1 knockdown on the proliferation, cell cycle progression, apoptosis, migration, and invasion of laryngeal cancer cells were evaluated by the CCK-8, colony formation, flow cytometry, Transwell migration, and western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Combination therapy with a PD-L1 inhibitor and AGK2 resulted in further increases in antitumor immunity. An association between FGL1 inhibition and antitumor immune responses has been reported in other studies ( 1 , 3 ). Wang et al ( 3 ) implanted FGL1-knockout mice with colon cancer cells and found diminished tumor growth compared with controls.…”
Section: Fgl1 and Antitumor Immunitysupporting
confidence: 81%
See 4 more Smart Citations
“…Combination therapy with a PD-L1 inhibitor and AGK2 resulted in further increases in antitumor immunity. An association between FGL1 inhibition and antitumor immune responses has been reported in other studies ( 1 , 3 ). Wang et al ( 3 ) implanted FGL1-knockout mice with colon cancer cells and found diminished tumor growth compared with controls.…”
Section: Fgl1 and Antitumor Immunitysupporting
confidence: 81%
“…One important consideration is whether tumor cell death and improved survival in this study were caused by DNA damage incurred by HDAC inhibition rather than via antitumor immunity — indeed, the authors did not assess DNA damage ( 4 ). However, the authors did demonstrate enhanced tumor invasion by immune cells in response to FGL1 acetylation ( 4 ), and past research has shown FGL1–LAG-3 interaction ( 1 , 3 ). Thus, it is likely that antitumor immunity at least plays a role in these findings.…”
Section: Acetylation-mediated Cancer Therapymentioning
confidence: 90%
See 3 more Smart Citations